PERCEPTION OF CORRUPTION, PERCEPTION OF TAX COMPLEXITY, AND FINANCIAL INFORMATION ACCESS: EXTENDING THE ANALYSIS OF THE SLIPPERY SLOPE FRAMEWORK - Mardhiah (Scientax, 2021)
Tax literature indicates perception of corruption and perception of tax complexity as tax compliance factors. Nevertheless, although the initial SSF theory suggests several tax compliance factors to have associations with trust in and power of tax authorities, none of the SSF studies pay their attention on these two factors. Therefore, based on survey questionnaires on 500 individual taxpayers in Jakarta, Indonesia, as well as interviews on several taxpayers and tax officers in the Directorate General of Taxes (DGT), this study is dedicated to elaborating the associations between these factors and trust and power and how the change in financial information access affects them. Mixed methods research was used through conducting a survey of individual taxpayers, and interviewing both individual taxpayers and tax officers. The results show that the factors are proven to have significant influence on trust in and power of the tax authorities, even though there is no significant association between perception of tax complexity and power. The results also confirm main SSF assumptions that trust leads to voluntary compliance while voluntary compliance positively affects overall tax compliance. Yet, the study fails to evidence the relationship of power to enforced compliance, while enforced compliance is found to negatively affects overall tax compliance.